Engineering characterisation of weathered rock at Sri Jaya, Pahang, Malaysia - Haryati, Awang; A F, Salmanfarsi; A, Arizam; Mohamad Idris, Ali (IOP Science, 2021)
Erosion and weathering are major processes that may reduce the strength of rock slope material or may cause significant change in the physical state of the slope. These can lead to landslide or slope failure, bringing significant risk in terms of properties damage and/or human safety. In Sri Jaya, Pahang, a large body of granite is exposed as cut rock slope, which shows different zones of weathering grade. Field and laboratory tests were carried out to determine the mechanical properties and the physical properties of weathered rocks of the slope, which involved a number of testing for the Schmidt rebound hammer test, point load test, moisture content, water absorption and specific gravity. From the tests, the study has determined the engineering properties of weathered rock of the slope where weathering grade and engineering properties of rock were correlated. A strong correlation was found between the weathering grade and engineering properties where they showed significant correlations for this site. It is proven that the engineering properties could be used as reliable parameters in determining the weathering grade of material in the field.